Representasi Gus dalam Novel Romansa Islami di Platform Sastra Siber Fizzo - Fahmy, Zulfa; Nuryatin, Agus; Supriyanto, Teguh (GERAM, 2024)
This research aims to determine the representation of the figure 'Gus' in Islamic romance novels on the Fizzo cyber literary platform. The phenomenon of Islamic romance novels that make 'Gus' the central character is increasingly widespread on the Fizzo cyber literary platform. Gus is a character created by the author with various characters that are different from reality. The research method used is qualitative, analyzing two novels, namely "Sesakit Itukah Mencintaimu, Gus" by Lutfiana Lut and "Meluluhkan Hati Gus Dingin" by Rara_za, as data sources. The results of the analysis show that the figure 'Gus' in these novels is represented as a figure who is physically and socially perfect, has a mysterious aura, and shows a strong humanist side. However, an important finding from this research is that the representation of the figure 'Gus' in Islamic romance novels is more often used as a strategy to gain popularity among readers. The figure of 'Gus' in these novels does not fully reflect the reality of the position of 'Gus' in Indonesian Islamic boarding school culture, where 'Gus' is supposed to have a deeper and more complex role in the social and religious context. Thus, this research provides insight into how cyber literature utilizes the character 'Gus' for commercial purposes while highlighting the incompatibility of representation with the reality of Islamic boarding school culture in Indonesia.